ANALISIS PENGELOLAAN SAMPAH DI KABUPATEN BANTUL TERKAIT RENCANA AKSI DAERAH UNTUK MEWUJUDKAN GERAKAN BANTUL BERSIH SAMPAH TAHUN 2025 - rahayu, esti (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2022)
The problem of waste is no longer just a problem of cleanliness and the environment, but has become a social problem that can cause conflict. In 2021, the potential waste generation in Bantul Regency is 197,895.34 tons/year, managed waste is 122,315.54 tons/year or 61.81%; still leaves 75,579.79 tons/year of household waste and household waste that has not been managed properly and correctly. This shows that the waste has not been managed properly. Therefore, this study aims to determine: (1) the profile of waste management in Bantul Regency; (2) the condition of BUMKal in Bantul Regency; (3) waste management problems in Bantul Regency; (4) the potential for the development of waste management in Bantul Regency, and (5) a regional action plan to realize the Clean Waste Bantul Movement. The research method used is a qualitative method. The data was obtained by discussing the selected informants by purposive sampling, observation and literature study. The research was conducted by understanding the condition of waste management in Bantul Regency, identifying and understanding the existing problems. The results of the analysis of waste management in Bantul Regency are: (a) the waste management is not optimal at the household, RT, RW, or village levels; (b) the role of BUMKal in waste management at the village level is not yet optimal; (c) the problems of waste management in Bantul Regency are as follows: people's habits of littering/burning garbage, the segregation of waste is not optimal from the source, the functioning of the waste bank is not optimal, the functioning of the TPS3r managed by KSM or BUMKal is not optimal, and the empowerment of the informal sector is not optimal. such as pelapak/scavengers, not yet optimally operated compost houses in the markets, the availability of new 18.5% waste collection points, the absence of TPST in Bantul Regency; (d) the potential for developing waste management in Bantul is high and can be directed to animal feed ingredients, compost, handicrafts, or processed into energy sources; (e) regional action plans to realize the Joint Bantul Movement can be pursued by optimizing waste processing facilities and infrastructure, increasing community development, building TPST/ITF/TPS3R, procurement of transportation fleet units.